Períodos de interferência de plantas daninhas infestantes do milho - Bagnara, Maico André Michelon (2017)
When competing with crops, weeds damage their growth and consequently reduce grain yield. In this sense, the purpose of this work was to determine the periods of interference; PAI (pre-interference period), PTPI (total interference prevention period), and PCPI (critical interference prevention period), papuan weeds (Urochloa plantaginea) and crabgrass (Digitaria ciliares) maize weeds. The experiment was conducted in a randomized block design with four replications, under no - tillage system. The treatments used consisted of maize growing with papaya and maize for increasing periods of 0, 7, 14, 21, 28, 35 and 42 days after emergence (DAE) of the crop and corn being kept free of With weeds in the same periods. Weeds, crabgrass and papua, corn weeds originated from the soil seed bank, with an average density of 215 and 87 plants m-2, respectively. At 42 DAE was determined the dry mass of the weeds and also of the crop, as well as the height of the corn plants the pre-harvest of the corn were collected 10 plants per experimental unit to determine the length of spikes, number of rows of grains by the number of grains per row of the spike, and productivity was obtained by harvesting three central lines from each experimental unit. Considering a 5% tolerance in the reduction of production, it was concluded that the PAI was 0 and 17 DAE, the PTPI from 0 to 32 DAE and the PCPI from 17 to 32 DAE under the conditions in which the experiment was performed.